A proposed solution to the crack-like flaws in hot forging process based on numerical simulations with LS-DYNA - Topa, Ameen
An important concern in metal forming process is whether the desired deformation can be accomplished without defects in the final product. These defects which may occur on the surface or within the product are due to the complex nature of the hot forging processes. The hot forging process is controlled by many parameters which include the temperature of the workpiece, the dies geometry, and the compression rate. As a result, experimental approach is ineffective in the investigation and elimination of the defects. Various theoretical fracture criteria have been developed and experimentally verified for a limited number of cases of forging processes. These criteria are highly dependent on the geometry of the workpiece and cannot be utilized for complicated shapes without prior experimental verification. However, experimental work is a resource hungry process. This study proposes the usage of the finite element analysis (FEA) software LS-DYNA to pinpoint the crack-like flaws in bulk metal forming products. Two different approaches named as the Arbitrary Lagrangian Eulerian (ALE) and smooth particle hydrodynamics (SPH) formulations were adopted. The results of the numerical simulations agree well with the experimental work as the final geometry and dimensions of the workpiece were accurately achieved. A comparison between the two formulations has been carried out to investigate the pros and cons of each method. Both formulations successfully predicted the flow of workpiece material and the plastic deformation during hot forging. However, only ALE method was able to approximate the location of the flaws. The numerical simulations reveal that the uneven thickness of the product disturbs the plastic flow of the material which increases the stress levels and results in the formation of the flaws. A parametric study was carried on to obtain the optimum wall thickness, compression rate, and process temperature. The application of these suggested values in the numerical simulations eliminated the occurrence of the flaws in the product.